2020
DOI: 10.3390/plants9050594
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Promotes Bolting and Flowering via the Floral Integrators RsFT and RsSOC1-1 under Marginal Vernalization in Radish

Abstract: Gibberellic acid (GA) is one of the factors that promotes flowering in radish (Raphanus Sativus L.), although the mechanism mediating GA activation of flowering has not been determined. To identify this mechanism in radish, we compared the effects of GA treatment on late-flowering (NH-JS1) and early-flowering (NH-JS2) radish lines. GA treatment promoted flowering in both lines, but not without vernalization. NH-JS2 plants displayed greater bolting and flowering pathway responses to GA treatment than NH-JS1. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…Gibberellic acids (e.g., GA 3 ) normally increase source strength by improv-ing photosynthetic efficiency and improve sink strength by redistributing photosynthetically assimilated products from leaves to buds (Iqbal et al, 2011;Verma et al, 2017). RNA-seq and qPCR analyses to investigate the effect of exogenous GA 3 (0, 1, or 10 mM) treatment on global gene expression profiles of radish (Raphanus sativus) revealed that 21 and 8 differentially expressed genes were identified as flowering time-and GA-responsive genes, respectively (Jung et al, 2020). Given that GA 3 (50 mg L -1 ) application reduced the production cycle by 6.2% compared to the control (71.5 vs. 76.2 days) while maintaining high flower quality, we believe that foliar application of 50 mg L -1 GA 3 is of great interest for the cut flower industry.…”
Section: Resultsmentioning
confidence: 99%
“…Gibberellic acids (e.g., GA 3 ) normally increase source strength by improv-ing photosynthetic efficiency and improve sink strength by redistributing photosynthetically assimilated products from leaves to buds (Iqbal et al, 2011;Verma et al, 2017). RNA-seq and qPCR analyses to investigate the effect of exogenous GA 3 (0, 1, or 10 mM) treatment on global gene expression profiles of radish (Raphanus sativus) revealed that 21 and 8 differentially expressed genes were identified as flowering time-and GA-responsive genes, respectively (Jung et al, 2020). Given that GA 3 (50 mg L -1 ) application reduced the production cycle by 6.2% compared to the control (71.5 vs. 76.2 days) while maintaining high flower quality, we believe that foliar application of 50 mg L -1 GA 3 is of great interest for the cut flower industry.…”
Section: Resultsmentioning
confidence: 99%
“…GAs also stimulate expression of MdTFL1 in apple ( Zhang et al., 2019 ). In contrast, the expression levels of RsFT and RsSOC1-1 are up-regulated after GA treatment in early-flowering (NH-JS2) Raphanus sativus (radish; Jung et al., 2020 ). Recently, a GA-DELLA (SLR1)-VvmiR159c- VvGIBBERELLIN MYB GENE ( GAMYB ) cascade was reported to modulate grape floral development ( Wang et al., 2018b ).…”
Section: Reproductive Growthmentioning
confidence: 97%
“…There has always been a dilemma on the plant hormones’ exact role in regulating the flowering process—for example, GA has been positively correlated with flowering in several plant species like Arabidopsis , tobacco, radish, etc . ( Gallego-Giraldo et al., 2007 ; Porri et al., 2012 ; Jung et al., 2020 ; Fukazawa et al., 2021 ), and contrary to many perennial fruit species, it inhibits flowering in apples, grapes, and citrus ( Boss and Thomas, 2002 ; Garmendia et al., 2019 ; Zhang et al., 2019 ). GA has been shown to affect the different phases of flowering, from flowering induction to flower development ( Mutasa-Göttgens and Hedden, 2009 ).…”
Section: Introductionmentioning
confidence: 99%